2021
DOI: 10.1101/2021.03.05.21252975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

North Carolina macular dystrophy: phenotypic variability and computational analysis of disease-implicated non-coding variants

Abstract: Purpose: North Carolina macular dystrophy (NCMD) is an autosomal dominant, congenital disorder affecting the central retina. Here, we report clinical and genetic findings in three families segregating NCMD and use epigenomic datasets from human tissues to gain insights into the effect of NCMD-implicated variants. Methods: Clinical assessment and genetic testing were performed. Publicly-available transcriptomic and epigenomic datasets were analyzed and the 'Activity-by-Contact' (ABC) method for scoring enhancer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…However, this necessitates improved methods for interpreting the spectrum of functional variation across all genes and particularly in the interpretation of non-coding variation, an area of investigation still in its infancy but beginning to make headway. Indeed, disruption of non-coding topologically associated domains have been associated with limb malformations (Lupiáñez et al, 2015;Spielmann et al, 2018), and non-coding variants upstream of PRDM13 and CCNC have been linked to North Carolina macular dystrophy (Small et al, 2016;Green et al, 2021). While efforts like the Atlas of Variant Effect Alliance are working toward achieving the mammoth goal of interpreting the impact of all genomic variation, there is still a long way to go (Matreyek et al, 2018;Jepsen et al, 2020).…”
Section: Looking To the Futurementioning
confidence: 99%
“…However, this necessitates improved methods for interpreting the spectrum of functional variation across all genes and particularly in the interpretation of non-coding variation, an area of investigation still in its infancy but beginning to make headway. Indeed, disruption of non-coding topologically associated domains have been associated with limb malformations (Lupiáñez et al, 2015;Spielmann et al, 2018), and non-coding variants upstream of PRDM13 and CCNC have been linked to North Carolina macular dystrophy (Small et al, 2016;Green et al, 2021). While efforts like the Atlas of Variant Effect Alliance are working toward achieving the mammoth goal of interpreting the impact of all genomic variation, there is still a long way to go (Matreyek et al, 2018;Jepsen et al, 2020).…”
Section: Looking To the Futurementioning
confidence: 99%
“…Our ability to detect pathogenic genomic variants from high-throughput sequencing data sets has expanded in recent years to include a wide range of mechanisms, including large structural genomic variants,29 30 deletions and duplications within single genes (‘exonic deletions),31 32 variants deep within introns that may cause aberrant mRNA splicing,33–36 variants in regulatory regions37–39 and complex alleles that comprised combinations of genomic variants 40 41. This requires a high level of specialist knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the recent elucidation of DYNC2H1 as a cause of inherited ophthalmic conditions was not captured in our initial curation process but can be subsequently included in EyeG2P analysis through addition of a single data line to the released EyeG2P datafile. 25 Our ability to detect disease-causing genomic variants from high-throughput sequencing datasets has expanded in recent years to include complex structural variants, 26,27 exonic deletions and duplications, 28,29 deeply intronic variants causing aberrant splicing, [30][31][32][33] variants in regulatory regions [34][35][36] and complex alleles comprised of combinations of genomic variants common in the general population. 37,38 Here we found that, in addition to characterizing novel exonic variants, EyeG2P is capable of prioritizing these diverse types of disease-causing variation, achieving 99.5% sensitivity in comparison to routine analytical approaches (Figure 1).…”
Section: Discussionmentioning
confidence: 99%